A Gaia DR2 Mock Stellar Catalog. (21st May 2018) - Rybizki, Jan; Demleitner, Markus; Fouesneau, Morgan; Bailer-Jones, Coryn; Rix, Hans-Walter; Andrae, René
Abstract: We present a mock catalog of Milky Way stars, matching in volume and depth the content of the Gaia data release 2 (GDR2). We generated our catalog usingGalaxia, a tool to sample stars from a Besançon Galactic model, together with a realistic 3D dust extinction map. The catalog mimics the complete GDR2 data model and contains most of the entries in the Gaia source catalog: five-parameter astrometry, three-band photometry, radial velocities, stellar parameters, and associated scaled nominal uncertainty estimates. In addition, we supplemented the catalog with extinctions and photometry for non- Gaia bands. This catalog can be used to prepare GDR2 queries in a realistic runtime environment, and it can serve as a Galactic model against which to compare the actual GDR2 data in the space of observables. The catalog is hosted through the virtual observatory GAVO's Heidelberg data center (http://dc.g-vo.org/tableinfo/gdr2mock.main ) service, and thus can be queried usingADQL as for GDR2 data.